ANALISIS YURIDIS TERHADAP PENERAPAN UNSUR DILAMPAUINYA BAKU MUTU LINGKUNGAN DALAM PUTUSAN HAKIM PADA KASUS KEBAKARAN LAHAN - Sormin, Yohanes Untung; Kadaryanto, Bagio; Harahap, Irawan (Collegium Studiosum Journal, 2025)
The objective of this research is to analyze the Juridical Analysis of the Application of the Element of Exceeding Environmental Quality Standards in Judges’ Decisions on Land Fire Cases, and to examine the legal consequences arising from such application. The method used is normative legal research. Based on the research findings, it is known that the juridical analysis of the application of the element of exceeding environmental quality standards in judicial decisions on land fire cases shows that this element plays a central role in proving the occurrence of environmental pollution or damage. Environmental quality standards serve as objective benchmarks established through regulation to determine whether the environmental condition remains within acceptable limits or has been polluted. In land fire cases, the exceedance of air, soil, or water quality standards becomes strong evidence that an environmental law violation has occurred. However, in judicial practice, the application of this element remains suboptimal. Many court decisions have not used scientific test results related to environmental quality standards as a primary legal consideration. This is due to several factors, including the limited technical capacity of law enforcement officers, weak scientific evidence presented by investigators and prosecutors, and the lack of judges' understanding of technical aspects in environmental law. As a result, many perpetrators of land fires, particularly corporations, are not held fully accountable under the law. Legal consequences of applying the element of exceeding environmental quality standards in judicial decisions on land fire cases include criminal sanctions, the application of the strict liability principle, obligations for compensation and environmental restoration, and administrative sanctions such as revocation of business licenses or suspension of activities